Agrilus (Agrilus) sundholmi, a new Agrilus from Australia (Coleoptera: Buprestidae) - Curletti, Gianfranco (Zootaxa, 2009)
A revision of the continental Australian species in the genus Agrilus Curtis, 1825 (Curletti, 2001, and supplements in 2002 and 2003) clarified the taxonomy, described two new subgenera, and described new taxa increasing the known Australian taxa to 47. Subsequently, five additional species have been described (Curletti 2007, 2008). Considering the size of the Australian mainland, and the cosmopolitan diversity of Agrilus (some 2700+ described species), the genus is poorly represented in Australia. Recent field work by entomological enthusiasts in central New South Wales has brought to light another new species, and increases the total number of Australian species of Agrilus to 53.